Mutations in TCF12, encoding a basic helix-loop-helix partner of TWIST1, are a frequent cause of coronal craniosynostosis. - Sharma, V; Fenwick, A; Brockop, MS; McGowan, S; Goos, J; Hoogeboom, A; Brady, A; Jeelani, N; Lynch, SA; Mulliken, J; Murray, D; Phipps, J; et al. (2013)
Craniosynostosis, the premature fusion of the cranial sutures, is a heterogeneous disorder with a prevalence of ∼1 in 2,200 (refs. 1,2). A specific genetic etiology can be identified in ∼21% of cases, including mutations of TWIST1, which encodes a class II basic helix-loop-helix (bHLH) transcription factor, and causes Saethre-Chotzen syndrome, typically associated with coronal synostosis. Using exome sequencing, we identified 38 heterozygous TCF12 mutations in 347 samples from unrelated individuals with craniosynostosis. The mutations predominantly occurred in individuals with coronal synostosis and accounted for 32% and 10% of subjects with bilateral and unilateral pathology, respectively. TCF12 encodes one of three class I E proteins that heterodimerize with class II bHLH proteins such as TWIST1. We show that TCF12 and TWIST1 act synergistically in a transactivation assay and that mice doubly heterozygous for loss-of-function mutations in Tcf12 and Twist1 have severe coronal synostosis. Hence, the dosage of TCF12-TWIST1 heterodimers is critical for normal coronal suture development.